2007
DOI: 10.1007/s00436-007-0666-9
|View full text |Cite
|
Sign up to set email alerts
|

Description of a new lung fluke species, Paragonimus vietnamensis sp. nov. (Trematoda, Paragonimidae), found in northern Vietnam

Abstract: Based on morphology of metacercariae and adult worms together with molecular data from our previous study, we describe herein a new lung fluke species named Paragonimus vietnamensis sp. nov. Metacercariae of this new species is round and extremely large in size (nearly 800 mum in diameter) having a fragile outer cyst of variable thickness and a thin fragile inner cyst. There are little or no space between metacercaria and the inner cyst wall. These and other morphological features of metacercariae of P. vietna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 6 publications
0
16
0
1
Order By: Relevance
“…In this study, we could add Vietnam as the endemic area of P. bangkokensis. This is the fifth Paragonimus species proven to be endemic in Vietnam following P. heterotremus (Kino et al 1995), P. vietnamensis (Doanh et al 2007b), P. proliferus (Doanh et al 2008), and P. westermani (Doanh et al 2009). Whether P. harinasutai exists or not in Vietnam needs more extensive survey.…”
Section: Discussionmentioning
confidence: 97%
“…In this study, we could add Vietnam as the endemic area of P. bangkokensis. This is the fifth Paragonimus species proven to be endemic in Vietnam following P. heterotremus (Kino et al 1995), P. vietnamensis (Doanh et al 2007b), P. proliferus (Doanh et al 2008), and P. westermani (Doanh et al 2009). Whether P. harinasutai exists or not in Vietnam needs more extensive survey.…”
Section: Discussionmentioning
confidence: 97%
“…During epidemiological surveys in Vietnam, in addition to P. heterotremus, we have found two more Paragonimus species, P. vietnamensis (Doanh et al 2007a) and P. proliferus (Doanh et al 2008) in northern mountainous area of this country. The present results added P. westermani as the fourth Paragonimus spp.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we found large encysted metacercariae of about 700-800 μm in diameter in mountainous crabs, Potamiscus tannanti and Potamiscus mieni, in northern Vietnam (Doanh et al 2007a), which was identified later as a new species, Paragonimus vietnamensis sp. nov., by morphology and molecular genetic analyses of metacercariae and adult worms (Doanh et al 2007b). Here we describe our new discovery of unusually large excysted metacercariae found in mountainous crabs, P. mieni, collected at Sinho district, Laichau province, northern Vietnam.…”
Section: Introductionmentioning
confidence: 99%